Why presidents fail and how they can succeed again - Kamarck, Elaine Ciulla (Washington, D.C Brookings Institution Press, 2016)
At the beginning of the century, the majority of Americans were satisfied with the way things were going in the United States. And then a slow decline began, seemingly uninterrupted by changes in party or achievements by the White House. As the campaigning for the next president begins, the question we ask ourselves now is who will be the most competent leader? In Why Presidents Fail and How They Can Succeed Again, Elaine Kamarck asks another important question: When did Americans lose faith in their leaders? And how can they get it back?
Includes bibliographical references (pages 155-170) and index.
Keywords: Presidents--United States